2004
DOI: 10.1152/japplphysiol.00511.2003
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength training with nonrespiratory maneuvers

Abstract: The diaphragm and abdominal muscles can be recruited during nonrespiratory maneuvers. With these maneuvers, transdiaphragmatic pressures are elevated to levels that could potentially provide a strength-training stimulus. To determine whether repeated forceful nonrespiratory maneuvers strengthen the diaphragm, four healthy subjects performed sit-ups and biceps curls 3-4 days/wk for 16 wk and four subjects served as controls. The maximal transdiaphragmatic pressure was measured at baseline and after 16 wk of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 26 publications
2
40
0
1
Order By: Relevance
“…However, due to the limitation of devices, we failed to obtain other parameters such as total lung capacity, transdiaphragmatic pressure and diaphragm thickness, which are more specific to indicate respiratory muscle and pulmonary function. Studies have reported that respiratory muscle training significantly increase transdiaphragm pressure [10], diaphragm thickness and total lung capacity [24]. Future studies should include more sensitive measurements to obtain valid data.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, due to the limitation of devices, we failed to obtain other parameters such as total lung capacity, transdiaphragmatic pressure and diaphragm thickness, which are more specific to indicate respiratory muscle and pulmonary function. Studies have reported that respiratory muscle training significantly increase transdiaphragm pressure [10], diaphragm thickness and total lung capacity [24]. Future studies should include more sensitive measurements to obtain valid data.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have suggested that abdominal exercises may not only improve abdominal muscle strength, but also affect the diaphragm and inspiratory muscles [9,12,13]. DePalo found that abdominal exercise significantly increases transdiaphragmatic pressure that results in an increase in PImax and PEmax in healthy adults [10]. Summerhill found that active elderly subjects have higher PEmax and PImax compared to those in sedentary subjects [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sit-ups, may increase respiratory muscle strength. 11 In addition, it has been observed that abdominal muscle training protocols, both passive (based on electrical stimulation) 12,13 and active, may be effective to improve respiratory muscle strength and forced expiratory flows.…”
Section: Introductionmentioning
confidence: 99%
“…Ao realizar manobras que aumentam a pressão intra-abdominal, o diafragma é ativado para minimizar a transmissão de alta pressão intra-abominal ao tórax. 27,28 Contraditoriamente aos resultados encontrados no presente estudo, onde houve variação significativa apenas da PEmax, Summerhill et al 7 encontraram melhora tanto da PImax quanto da PEmax de idosos. Segundo os mesmos autores, os idosos ativos rotineiramente envolvidos em atividades vigorosas que elevavam a pressão intra-abdominal tendem a fortalecer tanto o diafragma quanto a musculatura abdominal.…”
unclassified